Inductive Programming Meets the Real World - Gulwani, Sumit; Hernández-Orallo, José; Kitzelmann, Emanuel; Muggleton, Stephen H.; Schmid, Ute; Zorn, Ben (Communications of The ACM, 2015)
Since most end users lack programming skills they often spend considerable time and effort performing tedious and repetitive tasks such as capitalizing a column of names manually. Inductive Programming has a long research tradition and recent developments demonstrate it can liberate users from many tasks of this kind.